Silver nanoparticle modified carbon fiber-reinforced polymer material for resistance against thermal damage induced by irradiation. (April 2021) - Schuster, Thomas J; Weller, Lars; Wolfrum, Johannes; Eibl, Sebastian
We investigated the resistance of carbon fiber-reinforced plastics (CFRP) to thermal radiation when silver nanoparticles are added to the resin. An epoxy based CFRP material filled with up to 10 wt.% silver nanoparticles, with respect to the polymer matrix, shows an increase in time to ignition of up to ∼ 30% when irradiated from one side with an electrical heater with heat fluxes of 35 and 80 kW/m 2 . Scattering and specular reflectance of infrared light was analyzed before thermal irradiation, showing enhanced scattering of samples with increasing silver particle content, which correlates linearly to the time to ignition. The reaction to fire properties of the CFRP, analyzed by cone calorimetry, are also influenced positively by the silver nanoparticles. The thermal conductivity, as measured by laser-flash-analysis, shows no influence by the nanoparticles. Therefore, the increase in time to ignition, as well as the more homogeneous combustion, are not due to changes in conductivity, but to scattering and reflection effects caused by the nanoparticles. The modified material shows no decline in interlaminar shear strength, representing structural properties. Health and environmental risks by nanoparticle release during production, combustion, and machining of the modified CFRP are also investigated. The preliminary results show no additional hazards.